2021
DOI: 10.1021/acsanm.1c00345
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Pd–TiO2 Deactivation during H2 Production from Photoreforming Using Cu@Pd Nanoparticles Supported on TiO2

Abstract: Different Cu@Pd–TiO2 systems have been prepared by a two-step synthesis to obtain a bimetallic co-catalyst for the H2 photoreforming reaction. We find that the tailored deposition of Pd covering the Cu nanoclusters by a galvanic replacement process results in the formation of a core@shell structure. The photocatalytic H2 production after 18 h is 350 mmol/g on the Cu@Pd1.0–TiO2 bimetallic system, which is higher than that on the monometallic ones with a H2 production of 250 mmol/g on Pd-supported TiO2. Surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…Based on this, it can be proposed that Pd/TiO 2– x possesses a more robust SMSI effect compared with Pd/TiO 2 catalyst. Peaks within the 450–550 °C range are the reduction of stable PdO with strong interaction with TiO 2 support, or PdO with high dispersion on TiO 2 or the Pd 2+ –V O –Ti 3+ complex. ,, The reduction of the Pd 2+ –V O –Ti 3+ complex occurs at 490 and 500 °C for the Pd/TiO 2– x and Pd/TiO 2 catalysts, respectively. Herein, the dispersion of the supported Pd species on these two catalysts cannot yet be inferred based solely on this peak, since this high temperature (higher than 450 °C at which the catalysts were prepared) itself can cause both sintering and the SMSI effect for the dispersed Pd metals.…”
Section: Resultsmentioning
confidence: 99%
“…Based on this, it can be proposed that Pd/TiO 2– x possesses a more robust SMSI effect compared with Pd/TiO 2 catalyst. Peaks within the 450–550 °C range are the reduction of stable PdO with strong interaction with TiO 2 support, or PdO with high dispersion on TiO 2 or the Pd 2+ –V O –Ti 3+ complex. ,, The reduction of the Pd 2+ –V O –Ti 3+ complex occurs at 490 and 500 °C for the Pd/TiO 2– x and Pd/TiO 2 catalysts, respectively. Herein, the dispersion of the supported Pd species on these two catalysts cannot yet be inferred based solely on this peak, since this high temperature (higher than 450 °C at which the catalysts were prepared) itself can cause both sintering and the SMSI effect for the dispersed Pd metals.…”
Section: Resultsmentioning
confidence: 99%
“…As was shown in the P25-based catalysts, the fact that no saturation in hydrogen production was observed indicates that an increase in MoS 2 loading could lead to even higher hydrogen productions than those observed. When irradiated with visible light (λ > 400 nm), the electrons of the AgNPs are excited due to the plasmon resonance and injected into the CB of the TiO 2 [17], producing holes in the AgNPs that serve as oxidation agents that could lead to oxygen production or to their being quenched by a sacrificial electron donor [25]. The electrons that were injected to the conduction band of TiO 2 are gained by the water molecules, and hydrogen is produced.…”
Section: Hydrogen Production By Water Splittingmentioning
confidence: 99%
“…As a solution to this problem, TiO 2 can be synthesized in different crystalline structures and forms and modified by adding noble metals to reduce the band gap and optimize the use of sunlight [7]. The incorporation of silver (Ag) nanoparticles on the surface of TiO 2 makes it possible to change the properties of the semiconductor and diminish the rapid recombination of the photogenerated charge carriers in the process, shifting the radiation absorption threshold to the visible region [17]. The reason for this behavior is the surface plasmon resonance effect and charge separation by the displacement of photoexcited electrons from the metal nanoparticles to the conduction band (CB) of TiO 2 [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have reported that noble metal NPs, such as Au, Pt, Ag, Rh, Ni-Pt, Pd, Cu-Pd, and Au-Pd have been reported resulting in enhanced overall photocatalytic activity by enhancing the electron-hole charge separation. [61][62][63][64][65][66][67][68][69][70][71] In this regard, SnS 2 nanostructures were synthesized by hydrothermal method and were in situ decorated with Ni as a cocatalyst having different concentrations of Ni i.e., 1 mol%, 2.5 mol%, 5 mol%, and 10 mol% through a simple thermal reduction method. The detailed physico-chemical characterisation and inuence of Ni loading on SnS 2 towards its photocatalytic performance were investigated.…”
Section: Introductionmentioning
confidence: 99%